The Battle of Vouillé, 507 CE Where France Began - Mathisen, Ralph W.; Shanzer, Danuta (Millennium-Studien / Millennium Studies, 2012)
This volume highlights the heretofore largely neglected Battle of Vouillè in 507 CE, when the Frankish King Clovis defeated Alaric II, the King of the Visigoths. Clovis` victory proved a crucial step in the expulsion of the Visigoths from Francia into Spain, thereby leaving Gaul largely to the Franks. It was arguably in the wake of Vouillè that Gaul became Francia, and that "France began." The editors have united an international team of experts on Late Antiquity and the Merovingian Kingdoms to reexamine the battle from multiple as well as interdisciplinary perspectives. The contributions address questions of military strategy, geographical location, archaeological footprint, political background, religious propaganda, consequences (both in Francia and in Italy), and significance. There is a strong focus on the close reading of primary source-material, both textual and material, secular and theological.